Clinical course of Immunoglobulin A nephropathy with crescents in a multi‐ethnic Southeast Asian cohort. Issue 9 (8th June 2020) - Lim, Cynthia C.; Baikunje, Shashidhar; Choo, Jason C. J.; Tan, Puay H.; Foo, Marjorie; Woo, Keng T.
Abstract: Aim: Clinical presentation and course of Immunoglobulin A nephropathy vary by ethnicity and geography and significance of extracapillary proliferation or crescents (IgAN‐C) in Southeast Asia is not well described. We aimed to describe the clinical course of IgAN‐C in Singapore. Methods: Retrospective cohort study of adult biopsy‐proven IgAN diagnosed between February 2011 and October 2016 in 2 hospital‐based nephrology units. Outcome was chronic kidney disease (CKD) progression, defined as reduction in eGFR ≥50% or end stage renal failure (ESRF). Results: One hundred and forty‐five patients were studied. Among individuals with IgAN‐C (n = 44, 30%), 38 patients had cellular or fibrocellular crescents in 1 to 25% of the glomeruli and 6 had crescents in >25%. Median eGFR was 54 (33, 83) mL/min/1.73 m 2 . Compared to IgAN without crescents, IgAN‐C had greater proteinuria (median 2.9 [1.4, 5.4] g/g vs 1.9 [1.1, 3.6] g/g, P = .03) and more had endocapillary hypercellularity (96% vs 39%, P < .001). IgAN‐C were also more likely to receive immunosuppressants (66% vs 43%, P = .01) such as prednisolone (63% vs 38%, P = .006) and cyclophosphamide (12% vs 2%, P = .03). Median follow up was 27 (12, 46) months. IgAN‐C were more likely to achieve proteinuria reduction ≥50% at 6 months (66% vs 44%, P = .03). CKD progression within 12 months was not different among those with and without crescents (13% vs 10% respectively, P = .73). However, immunosuppressant treatment of IgAN‐C was associated with reduced ESRF (0 vs 20%, P = .03). Conclusion: Immunosuppressants may attenuate the risk of ESRF in IgAN‐C. SUMMARY AT A GLANCE: This study described the clinical course of crescentic IgA nephropathy in a retrospective cohort and found patient with any crescents was more likely to receive immunosuppressant treatment which may reduce ESKD risks.